Evolution of dislocation and twin densities in a Mg alloy at quasi-static and high strain rates. (December 2020) - Wang, M.; Xu, X.Y.; Wang, H.Y.; He, L.H.; Huang, M.X.
Abstract: The present work, for the first time, quantitatively studies the evolution of both dislocations and deformation twins with various strain rates in an ATZ311 Mg alloy. Interrupted tensile tests were performed at the strain rates of 0.001, 1 and 600 s −1 . Deformation twins were characterized by microscopy techniques and evaluated using the fractions of twin boundaries and twinned area. The average dislocation density and the relative fractions of dislocations with different Burgers vectors were determined from neutron diffraction data. It was found that the twin fraction increases remarkably and becomes saturated at lower strain rates (0.001-1 s −1 ), while the dislocation density only obtains an obvious enhancement at a much higher strain rate (600 s −1 ). Besides, the distinctively high flow stress at high strain rate leads to a substantial increase in the density of the hard-to-activate 〈 c + a 〉 -type dislocations, after the 〈 a 〉 -type dislocation density reaches rapidly its saturated value at a small strain level. The twinning modes with opposite polarities are able to coexist in the same grains because of the high local stress concentration at strain rates above 1 s −1 . Graphical abstract: Image, graphical abstract